Zanesljivost merjenja anteverzije vratu stegnenice pri otrocih s cerebralno paralizo - Gorišek Humar, Marta (Rehabilitacija (Ljubljana), 2012)
Background: One of the skeletal abnormalities frequently found in children with cerebral palsy (CP) is increased femoral neck anteversion (FNA). During clinical examination, FNA can be estimated in children with CP if passive range of motion (ROM) of internal and external hip rotation is measured, observed and compared, as well as by using the Trochanteric Prominent Angle Test (TPAT). The aim of the study was to assess reliability of the two methods for estimating FNA during clinical examination in children with CP. Methods: The participants were children with CP treated as outpatients or in-patients at the children's department of the University Rehabilitation Institute in Ljubljana between December 2009 and June 2010. Four series of measurements were performed with each child by four physiotherapists. Each series included goniometric measurement of passive ROM of internal and external hip rotation, followed by three consecutive measurements of FNA angle using the TPAT on both lower limbs. Results: Thirty-one children participated, 14 boys and 17 girls, aged 9 years on average. All the intra-class correlation coefficients, which were used for assessing intra- andinter-rater reliability of FNA angle measurement and passive ROM of internal and external hip rotation on the right and left side, were high (0.7 to 0.9). Conclusion: The results show that the methods for determining FNA angle during clinical examination in the addressed population are reliable. Hence, they are suitable and useful for clinical practice within rehabilitation.
Keywords: anteverzija kosti; anteverzija vratu stegnenice; Bone Anteversion; Cerebral Palsy; cerebralna paraliza; clinical measurement; femoral anteversion; klinične meritve; reliability; zanesljivost